Cat sitter among the pigeons [large type] : a Dixie Hemingway mystery - Clement, Blaize (Clement, Blaize. Dixie Hemingway mysteries., 2011)
Dixie Hemingway is caring for the cat of a prickly old man whose granddaughter shows up with a baby in tow. Dixie desperately tries to save this young woman and her infant from murderous con artists ready to kill in order to hold on to the millions they stole from naïve investors. The villains, though, are not run-of-the-mill criminals; they are among the socially prominent movers and shakers in Dixie's town. Now Dixie must confront her greatest fears and try to save the lives of the innocent, both two-legged and four.